Metal-organic framework-derived Ga-Cu/CeO2 catalyst for highly efficient photothermal catalytic CO2 reduction - Deng, Bowen; Song, Hui; Peng, Kang; Li, Qian; Ye, Jinhua (Applied catalysis. B, Environmental, 2021)
[Display omitted] •An efficient catalyst has been synthesized via MOF-templated method.•Photothermal catalytic CO production rate of Ga-Cu/CeO2 reaches 111.2 mmol g−1 h−1.•Photothermal heating and light-promotion contribute to the high activity.•The introduction of Ga enhances the formation of key intermediates. Photothermal catalytic CO2 reduction is an attractive process to efficiently convert solar energy into chemical energy with mitigation of global carbon emissions, but it remains a great challenge in achieving high conversion efficiency due to the limited sunlight capturing capacity and lack of highly efficient catalysts. Herein, we report a Ga-Cu/CeO2 catalyst synthesized by direct pyrolysis of the Ga and Cu-containing Ce-metal-organic frameworks for efficient photothermal catalytic CO2 hydrogenation. Because of the highly dispersed Ga and Cu species in CeO2, the optimized catalyst 10Cu5Ga/CeO2 (10 wt% Cu and 5 wt% Ga) achieved a CO production rate of 111.2 mmol g−1 h−1 with nearly 100 % selectivity under full solar spectrum irradiation, which is superior to most reported Cu and other earth-abundant metals-based photothermal catalysts. Mechanism studies demonstrated that the synergy of photothermal heating/conversion and light-promotion contributed to the substantially increased CO production. In situ DRIFTS results revealed that the introduction of Ga enhanced the formation of formate species, the key intermediates in CO2 hydrogenation, and light irradiation facilitated the decomposition of formate species to carbonyl, thus enhancing CO production. This work provides a potential strategy towards the synthesis of efficient catalysts for photothermal CO2 reduction.